2018
DOI: 10.1021/acsami.7b16730
|View full text |Cite
|
Sign up to set email alerts
|

Semitransparent Flexible Organic Solar Cells Employing Doped-Graphene Layers as Anode and Cathode Electrodes

Abstract: Semitransparent flexible photovoltaic cells are advantageous for effective use of solar energy in many areas such as building-integrated solar-power generation and portable photovoltaic chargers. We report semitransparent and flexible organic solar cells (FOSCs) with high aperture, composed of doped graphene layers, ZnO, P3HT:PCBM, and PEDOT:PSS as anode/cathode transparent conductive electrodes (TCEs), electron transport layer, photoactive layer, and hole transport layer, respectively, fabricated based on sim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(41 citation statements)
references
References 42 publications
1
40
0
Order By: Relevance
“…Although conventional opaque solar cells exhibit high efficiencies, they require dedicated space and additional installation efforts in the form of metal frame constructions on the roof or façade; a general disadvantage within the BIPV context ( Figure ). The research topic of semitransparent organic solar cells (OSCs) addresses the aforementioned issues by offering solutions, such as the implementation of flexible semitransparent OSCs into glass windows and roofs of new or existing buildings, greenhouses, vehicles, or mobile electronic devices, thereby transforming them into energy harvesting multifunctional units . Additionally, OSCs can be tuned to absorb specific frequencies such as UV, vis, or near‐IR and they can be easily integrated with other devices, such as to drive electrochromic devices that modulate the level of interior light …”
Section: Introductionmentioning
confidence: 99%
“…Although conventional opaque solar cells exhibit high efficiencies, they require dedicated space and additional installation efforts in the form of metal frame constructions on the roof or façade; a general disadvantage within the BIPV context ( Figure ). The research topic of semitransparent organic solar cells (OSCs) addresses the aforementioned issues by offering solutions, such as the implementation of flexible semitransparent OSCs into glass windows and roofs of new or existing buildings, greenhouses, vehicles, or mobile electronic devices, thereby transforming them into energy harvesting multifunctional units . Additionally, OSCs can be tuned to absorb specific frequencies such as UV, vis, or near‐IR and they can be easily integrated with other devices, such as to drive electrochromic devices that modulate the level of interior light …”
Section: Introductionmentioning
confidence: 99%
“…The 0.2 cm 2 graphene devices with the 30 nm MoO x interfacial layer had an average PCE of 5.2% with V oc = 0.87 V, J sc = 11.5 mA cm −2 , and FF = 51%. Taking into account the device dimensions, a PCE of 5.2% is amongst the best performance for OSCs with a graphene‐based anode, noting that previously reported devices are generally smaller . However, we found that there was still a performance gap between the devices containing the graphene TCEs and the control ITO‐based devices, which showed an averaged PCE of 8.7%, with a J sc of 14.1 mA cm −2 , a V oc of 0.88 V, and a FF of 69%.…”
Section: Resultsmentioning
confidence: 46%
“…Later, Shin et al fabricated semitransparent flexible OSCs using bis‐(trifluoromethanesulfonyl)‐amide (TFSA) and triethylene tetramine (TETA)‐doped graphene as anode and cathode, respectively (Figure 4b). [ 72 ] The PCE was further improved to 4.23% by adding an Al reflective mirror on the side of the device. The flexible device retained more than 99% of the initial PCE after the bending test with a radius of 12–6 mm.…”
Section: Flexible Organic Solar Cellsmentioning
confidence: 99%